O paradoxo de uma existência: a trajetória do Partido Trabalhista Brasileiro no Espírito Santo (1945-1964) - Cardoso, Lucian Rodrigues (2018)
The present dissertation has the main objective to analyze the trajectory and the institutionalization process of the Partido Trabalhista Brasileiro (Brazilian Labor Party) in the State of Espírito Santo between the years 1945 and 1964. The research is grounded on the need to study the political discourses and practices of the time, aiming to fill one of the gaps in political history of a peripheral state in the national political and economic development. In this way, a study that dialogs with the theses produced at the national level about the party is proposed, in order to detect congruences and dissonances with the local plan. To that end, it will be settled on a theory of party organization that contemplates the party’s decisions as crucial elements for apprehending its entire subsequent history. Therefore, the research proposed to investigate a political project which, in its initial program, was built mainly upon urban and working-class bases, with a reformist and leftist impetus from the 1960s. However, it is a question of studying this very project in an essentially agrarian and traditional state, where the clientelistic practices and a new political paradigm coexisted: the emergence of the working classes in the political scenario. The main hypothesis is that in an overdue and tardy state with regard to its capitalist development process, also characterized by its predominantly agrarian society and dominated by oligarchs, the PTB of Espírito Santo opted for patronage, spoils system and clientelism, when it attempted to compete with the local oligarchies. In view of this, there was a previous marked growth in organization and votes, which then suffered, during a great part of its course, with the most diverse disputes of interests for jobs and positions in the government autarchies. All the same, this scenario did not prevent leaders committed to the party program and attentive to the demands of the Espírito Santo workers, such as Mario Gurgel and Ramon de Oliveira Netto, from appearing in the party, although they were dominated by internal and external oppositions to the party, which joined it or silenced in the face of the coup and the civil-military dictatorship brought about in 1964.